Experimental evaluation of methanol steam reforming reactor heated by catalyst combustion for kW-class SOFC. (8th February 2023) - Hu, Yang; Han, Chuanjun; Li, Wenying; Hu, Qiang; Wu, Hongsong; Luo, Zixuan
Abstract: The distributed power generation of methanol steam reforming reactor combined with solid oxide fuel cell (SOFC) has the characteristics of outstanding economic advantages. In this paper, a methanol steam reforming reactor was designed which integrates catalyst combustion, vaporization and reforming. By catalyst combustion, it can achieve stable operation to supply fuel for kW-class SOFC in real time without additional heating equipment. The optimal operating condition of the reforming reactor is 523–553 K, and the steam to carbon ratio (S/C) is 1.2. To study the reforming performance, methanol steam reforming (MSR), methanol decomposition (MD), water-gas shift (WGS) were considered. Operating temperature is the greatest factor affecting reforming performance. The higher the reaction temperature, the lower the H2 and CO2, the higher the CO and the methanol conversion rate. The methanol conversion rate is up to 95.03%. The higher the liquid space velocity (LHSV), the lower the methanol conversion rate, the lowest is 90.7%. The temperature changes of the reforming reactor caused by the load change of stack takes about 30 min to reach new balance. Local hotspots within the reforming reactor lead to an excessive local temperature to test a small amount of CH4 in the reforming gas. The methanation reaction cannot be ignored at the operating temperature. The reforming gas contains 70–75% H2, 3–8% CO, 18–22% CO2 and 0.0004–0.3% CH4 . Trace amounts of C2 H6 and C2 H4 are also found in some experiments. The reforming reactor can stably supply the fuel for up to 1125 W SOFC. Highlights: The reforming reactor can operation to supply fuel for kW-class SOFC without additional heating equipment. The reforming reactor integrates catalyst combustion, vaporization and methanol steam reforming. Reaction temperature has the greatest impact on reforming performance than LHSV and S/C. In the reforming reactor, the methanation reaction should not be neglected, and trace amounts of C2 H6 and C2 H4 are found. The reforming reactor is verified to meet the operating of SOFC by experiments, which is available for up to 1125 W SOFC.